Diagnosis and Treatment of Cervical Intraepithelial Neoplasia with Carbon Dioxide Laser Therapy in Selected Patients - Al-Tawjery, Intisar H.; Jawad, Hussein A.; Mirdan, Balsam M. (Iraqi Journal of Laser, 2009)
Female infection with HPV (human papilla virus) has been established as an essential cause of CIN (cervical intraepithelial neoplasia). The danger of transformation from CIN to frank malignancy should be considered. Objective: The goal of this study is to evaluate the effectiveness of CO2 laser vaporization of ectocervical lesion high grade squamous intraepithelial lesion (HGSIL). Patients and Methods: Four Female out of 150 affected with HGSIL lesions were submitted to CO2 laser vaporization and followed up in 4 months later, and 10 women with HGSIL lesion submitted to electrocautery diathermy for the comparison. Results: Among women treated by CO2 laser vaporization, 3 women had negative results (clear cervix), at 4 months follow up; one woman had recurrence at 4 months following up, the recurrence was due to incomplete destruction of the deepest part of the lesion involving the glandular crypts. Conclusion: The preservation of the anatomical integrity of the cervical tissue offers a better follow-up of those patients. Although other treatment modalities are available, CO2 laser represents an acceptable surgical tool for the management of cervical intraepithelial neoplasia (CIN) with minimal complications.